Emerald grounds Muntinlupa City Center for Culture and the Arts - Cuenco, Zade Elijah G. author; Melgazo, Dylan James (Quezon City College of Architecture, University of the Philippines Diliman, 2018)
Emerald Grounds is a comprehensive design project located within New Bilibid Prison Reservation's Sunken Garden in Muntinlupa City. Aligned with the city's economic, social, and cultural needs, the study is rooted in five principal agendas namely (1) sense of identity, (2) economic development, (3) academic, (4) sustainability, and (5) social welfare. It will be a cultural center that translates Muntinlupa City's treasured history and culture alive through architectural expressions. Overall, the study aims to pay homage to the richness of Muntinlupa City. At the same time, it aspires to bring economic opportunities to the city and acknowledge a growing central business district. It will be done through a celebration of various activities while physically connecting to the city's adventurous terrain. In line with these goals and aspirations, Emerald Grounds is a forward thinking yet expressive cultural center that houses multiple programs and activities celebrating the history and people of Muntinlupa, and increase income-generating opportunities at the same time. The center will include spaces for leisure, commercial, performance, and exhibit galleries in order to provide an all-inclusive hub and welcoming destination for the public.
Include appendices
Thesis (Bachelor of Science in Architecture)--University of the Philippines Diliman
Keywords: Arts facilities; Arts facilities -- Muntinlupa City -- Philippines